A comparison study for active chilled beam and variable air volume systems for an office building / Tam Jun Hao - Tam, Jun Hao (2018)
Comparison in terms of energy and cost is carried out between two different air distribution systems: variable air volume (VAV) and active chilled beam (ACB) based on a virtual building. Cooling load calculation was performed to determine the total load demand and system design was carried out to determine the system capacity. All design steps were presented in detail for both systems based on appropriate design requirement in accordance with ASHRAE’s standards. Comparing to VAV, ACB is more complicated in terms of design as it involves specific design considerations such as room latent load shall not be too high, secondary chilled water temperature shall not be lower than the room dew point temperature and room shall have adequate ceiling space for the placement of chilled beam. Energy and cost analysis was done to determine which system gives better saving. From the results analysis, it shows that ACB is more energy-saving than VAV especially at full load and normal part-load conditions because of the reduced AHU fan’s capacity. In terms of cost, ACB has higher initial cost than VAV where it is mainly contributed by the secondary chilled water pipe, heat exchanger and the beam itself. However, the operation cost is lower for ACB and for long term use, ACB is more cost-saving than VAV. Since the results discussed in this thesis is obtained by numerical method, for future work, it’s recommended to perform energy audit on the actual building in order to verify the validity of the computed results.